A organização textual do gênero relato sob a perspectiva das relações retóricas - Santos, Hérica Ribeiro dos (2016)
This research aims to describe the report genre textual organization, adopting, as the analysis corpus, fifteen reports produced in an entrance exam conducted at the State University of Maringá (UEM). The theoretical perspectives adopted are based on the theory of genres considering the fact that this investigation has been researching for a relatively stable statement, embodied in daily life and socio-communicative properties; on the principles of Functionalism, specifically in the Rhetorical Structure Theory (RST), by the fact that it contributes in order to get subsidies to analyze the textual coherence through the relations established between the text portions. In this sense, the textual organization occurs by the constitution of the related topics, forming the text bigger parts, comprising it as a whole; and also through the Theory of Prototypes, by allowing identifying textual structures more typical of the report genre. The texts, after being digitalized, were segmented and submitted to the analysis with the assistance of a computational program, the RST Tool. After that, the results were analyzed in relation to the compositional genre structure. The analysis demonstrated that there is prototyping both in the rhetorical structure, because, in the macrostructure, the same relations show up cause, background, elaboration, although in different levels as well as in its compositional structure, since the majority of the texts analyzed included all the phases that arrange the report genre - title, the initial phase, the complication phase, the actions phases, the resolution phase, the final situation phase, the assessment phase and the moral phase. Some differences were verified in both structures of the report genre, the rhetorical and compositional. In the last one, there is the presence or absence of title as well as the assessment and moral phases; in the first one, the rhetorical relations position on the first and second levels of analysis. In this way, it was verified that the rhetorical relations are not only essential for the understanding of the organization of the text, as well as they manifest in favor of the reported facts linking.